2005
DOI: 10.1111/j.1445-2197.2005.03526.x
|View full text |Cite
|
Sign up to set email alerts
|

The Auburn Elective Surgery Pilot Project

Abstract: During the project period, the number of the selected surgical procedures performed doubled. Fifty-seven per cent of patients were discharged on the day of surgery. Surgeons took less time to perform procedures. By the end of the trial period, waiting lists for the selected procedures were eliminated. Operating costs as evaluated by the Centre for Health Economics Research and Evaluation were reduced by 25%. The administrative changes to surgical admissions resulted in improved cost and patient throughput for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 8 publications
1
32
0
2
Order By: Relevance
“…Single-entry models are based on queuing theory, and are well suited to services with variable wait times among consultants since patients waiting the longest can be booked into the next available appointment [10]. Although the evidence is mixed, some studies show that single-entry approaches can reduce waiting lists [10][11][12][13][14], increase the number of patients seen Page 5 [11,13,15], and improve access and efficiency of patient care with improved patient satisfaction in both surgical and outpatient settings [9][10][11]16]. Most centralized intake systems have focused on a homogenous patient population requiring a specific procedure [9][10][11]16].…”
Section: Pagementioning
confidence: 99%
“…Single-entry models are based on queuing theory, and are well suited to services with variable wait times among consultants since patients waiting the longest can be booked into the next available appointment [10]. Although the evidence is mixed, some studies show that single-entry approaches can reduce waiting lists [10][11][12][13][14], increase the number of patients seen Page 5 [11,13,15], and improve access and efficiency of patient care with improved patient satisfaction in both surgical and outpatient settings [9][10][11]16]. Most centralized intake systems have focused on a homogenous patient population requiring a specific procedure [9][10][11]16].…”
Section: Pagementioning
confidence: 99%
“…Relevant to this, an Audit Commission report on operating theatres published in 2002 involving 70 NHS Trusts in the UK showed that on average only 73% of the planned sessional operating hours are actually utilized. Although several retrospective (Hairat et al, 1990;Shushan et al, 1999;Broka et al, 2003;Pandit and Carey, 2006) and prospective studies (Bruwer, 1994;Schofield et al, 2005;Singh et al, 2005;Foley and Sodani, 2007) have addressed issues surrounding the organization and running of elective operating lists, no study so far has looked at each step of a patient's journey through the operating theatre systematically in order to identify factors which make this passage inefficient and lead to poor theatre utilization. We set out to do this as part of a prospective study with the hope of finding possible solutions to the problem of sub-optimal utilization of elective operating theatre time.…”
Section: Introductionmentioning
confidence: 97%
“…Included studies were published from 2002 to 2012. Seven studies were from Canada,24–30 three from UK and one from Australia 31. Three studies evaluated the use of SEMs for cardiac surgery, two for hernia, two for hip and knee replacement, one for spinal surgery, one for cataract removal and two studies for multiple elective procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Six detailed the implementation and effectiveness of SEMs,24 25 28 31–33 two simulated the outcomes of a potential implementation,27 30 two described the development of such an implementation26 28 and two assessed the views of physicians and/or patients regarding the use of SEMs 529…”
Section: Resultsmentioning
confidence: 99%